A counterfactual approach to measure the impact of wet grassland conservation on U.K. breeding bird populations. Issue 5 (1st June 2021) - Jellesmark, Sean; Ausden, Malcolm; Blackburn, Tim M.; Gregory, Richard D.; Hoffmann, Mike; Massimino, Dario; McRae, Louise; Visconti, Piero
Abstract: Wet grassland populations of wading birds in the United Kingdom have declined severely since 1990. To help mitigate these declines, the Royal Society for the Protection of Birds has restored and managed lowland wet grassland nature reserves to benefit these and other species. However, the impact of these reserves on bird population trends has not been evaluated experimentally due to a lack of control populations. We compared population trends from 1994 to 2018 among 5 bird species of conservation concern that breed on these nature reserves with counterfactual trends created from matched breeding bird survey observations. We compared reserve trends with 3 different counterfactuals based on different scenarios of how reserve populations could have developed in the absence of conservation. Effects of conservation interventions were positive for all 4 targeted wading bird species: Lapwing ( Vanellus vanellus ), Redshank ( Tringa totanus ), Curlew ( Numenius arquata ), and Snipe ( Gallinago gallinago ). There was no positive effect of conservation interventions on reserves for the passerine, Yellow Wagtail ( Motacilla flava ). Our approach using monitoring data to produce valid counterfactual controls is a broadly applicable method allowing large‐scale evaluation of conservation impact. Abstract : Article impact statement : Post hoc quasi‐experimental analysis shows that wet grassland conservation has positively affected targeted breeding bird populations. Abstract : Un Enfoque Hipotético para Medir el Impacto de la Conservación de Pastizales Húmedos sobre Poblaciones Reproductoras de Aves en el Reino Unido Resumen: Las poblaciones de aves zancudas en los pastizales húmedos del Reino Unido han declinado gravemente desde 1990. Para ayudar con la mitigación de estas declinaciones, la Real Sociedad para la Protección de las Aves ha restaurado y manejado las reservas naturales en pastizales húmedos de tierras bajas para beneficiar a estas y otras especies. Sin embargo, el impacto de estas reservas sobre las tendencias poblacionales de las aves no ha sido evaluado experimentalmente debido a la falta de poblaciones control. Comparamos las tendencias poblacionales entre 1994 y 2018 de cinco especies de aves de importancia para la conservación, que se reproducen dentro de estas reservas naturales, mediante tendencias hipotéticas creadas a partir de los censos de observación de aves reproductoras emparejadas. Comparamos las tendencias de las reservas con tres casos hipotéticos diferentes basados en diferentes escenarios de cómo las poblaciones de la reserva podrían haberse desarrollado en ausencia de la conservación. Los efectos de las intervenciones de conservación fueron positivos para las cuatro especies focales de aves zancudas: Vanellus vanellus, Tringa totanus, Numenius arquata y Gallinago gallinago . No hubo un efecto positivo de las intervenciones de conservación para la especie paserina Motacilla flava . Nuestra estrategia utilizando datos de monitoreos para producir controles hipotéticos válidos es un método ampliamente aplicable que permite ka evaluación del impacto de la conservación a gran escala 摘要: 自1990 年以来, 英国湿草地涉禽的数量急剧下降。为了缓解这些鸟类种群丧失, 英国皇家鸟类保护协会通过恢复和管理低地湿草地自然保护区来帮助保护这些鸟类及其它物种。然而, 由于缺乏对照种群, 保护区对鸟类种群动态的影响还没有得到实验评估。本研究将在这些保护区繁殖的五种受保护鸟类 1994–2018 年的种群动态与配对的鸟类繁殖调查获得的反事实动态进行了比较。我们比较了保护区鸟类种群动态与三种反事实动态, 这些反事实动态是基于保护区种群在没有保护的情况下如何发展的不同情景假设。结果表明, 研究关注的四种涉禽:凤头麦鸡 ( Vanellus vanellus ) 、红脚鹬 ( Tringa totanus ) 、白腰杓鹬 ( Numenius arquata ) 和扇尾沙锥 ( Gallinago gallinago ) 的保护措施均取得了积极成效, 而对保护区中雀形目鸟类黄鹡鸰 ( Motacilla flava ) 的保护干预没有积极作用。我们的方法利用监测数据产生了可靠的反事实对照, 是一种可用于大规模评估保护影响的广适性方法。【翻译: 胡怡思; 审校: 聂永刚】